Analisis keterampilan Guru Dalam Analisis keterampilan Guru Dalam Menjelaskan Materi Guna Membangun Keaktifan Belajar Siswa - Nuri, R Nurhayati; Suriyati, Suriyati; Nengsih, Diarti Andra (Dahzain Nur, 2023)
AbstractTeaching skills are very much needed in the student teaching and learning process. A teacher must master this when he wants to teach. Components that must be considered in applying explanation skills are the use of intonation, volume, expression, body movements, language, motivation and providing understanding of foreign terms in the learning material. Apart from that, it is also necessary to know what supporting and inhibiting factors influence students so that they are active and inactive in the explanations given by the teacher. These learning supports include learning interests, student needs, teacher personality as well as materials and environments that influence students. The aim of this research is to find out the intonation, volume, language and motivation used by teachers in carrying out explaining activities to students as well as the factors that support and hinder active and non-active students in the learning process. The research method used is qualitative research with a phenomenological approach. Data collection techniques include interviews, observation and documentation by applying data and time triangulation techniques. Data analysis uses collection, reduction, presentation and conclusion techniques. The results obtained are that explanation skills are greatly influenced by intonation, language style, volume and teacher motivation. Apart from that, it is also influenced by students' expressions, body styles and interest in learning which cannot be forced.Keywords: teaching skills, student learning activeness